Peace River District, Canada: Its Resources and Opportunities: - Canada Natural Resources Intelligence Branch (Author); Kitto, F. H. (Franklin Hugo), b. 1880 (Author) (F.A. Acland, printer, 1922)
by F.H. Kitto prepared under the direction of the Superintendent of the Natural Resources Intelligence Branch . Department of the Interior, Canada . In the preparation of this report valuable assistance has been received from officials of the federal departments. Mr. Charles Camsell, deputy minister of mines, and Mr. C.H. Attwood, of the Dominion Water Power Branch, have prepared the chapters dealing with mineral deposits and water powers, respectively. The Director of Experimental Farms, the Director of Forestry and the Commissioner of Dominion Parks have revised those portions of the report relating to their work.